Resident Attribution and Tourist Stereotypes. (May 2019) - Hsu, Cathy H. C.; Chen, Nan
The value of attribution theory in explaining and predicting resident perceptions of/reactions toward tourists is underestimated by tourism scholars. This article critically analyses the evolution and underdevelopment of attribution theory, as well as the literature on tourist stereotypes which serve as heuristics that may bias attribution. Under the guidance of dual process theories, a comprehensive conceptual framework is developed to delineate the interactions between a three-step resident attribution process of encounters with tourists and tourist stereotypes' activation, application/suppression, and modification. Potentially fruitful directions are suggested for future research. This conceptual article not only pioneers in establishing conceptual links between a tourism phenomenon and a social psychological theoretical development, but it also broadens the research paradigm of resident–tourist relationship studies.